ETNOMATEMATIKA PADA PETILASAN PRABU TAWANG ALUN DI ROWO BAYU BANYUWANGI SEBAGAI LEMBAR KERJA SISWA - Salamah, Umi; Susanto, Susanto; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2019)
Ethnomatematics is mathematics which found in the culture of the community where the community has unknowingly applied the concept of mathematics in the culture. The purpose of this research was to describe ethnomatematics in the petilasan prabu Tawang Alun building and produce student worksheets. This type of research is qualitative research with an ethnographic approach. There are four subjects of this research, namely one building administrator and three building carving experts. Data collection methods used are observation, interviews, documentation, and triangulation. This research focused on the stage, body, legs, stairs, and carvings on the petilasan prabu Tawang Alun building. The results of this study indicate the presence of ethnomatematics in the petilasan prabu Tawang Alun building. Geometry concepts or elements found include: flat shapes (triangles, squares, rectangles, circles, trapezoid), space structures (beams), congruent, and geometrical transformations (translation, reflection, and dilation. Ethnomatematics in this research will be made worksheets are intended for class IX in even semester with geometrical transformations material. Keyword : Ethnomatematics, petilasan prabu tawang alun, Geometry